Bloodreserving technology during surgical treatment of mitral valve disease - Popov, V. V.; Gumenyuk, B. N.; Gurtovenko, A. M.; Dyachenko, V. L.; Tihonenko, L. I.; Rudenko, E. V.; Lazorishinetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
Usage of donor blood during operations of mitral valve replacement with usage of donor blood components is associated with different possible complications, which stimulates to search measures for not using ше. In department of acquired heart diseases of NICVS AMS Ukraine from 01.01.2006. till 01.01.2009 were performed 317 isolated mitral valve replacements, in treatment of whom during hospital period components of donor blood were not used. Methodics of anesteological and perfusiological treatment in mitral valve replacemnt with cardiopulmonary bypass was described, and alsopeculiarities in intensive care unit. Hospital mortality was 1,4%, duration of stay in intensive care unit 54,2±4,7 hours, duration of stay in surgical department – 7,9±0,7 days. At discharge this group of patients had moderate anemia. Usage of developed methodics in clinical practice allowed to get good clinical effect, avoiding posttransfusion complications on hospital stage.